2021
DOI: 10.2147/jir.s292544
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Intestinal Barrier Damage in Psoriasis

Abstract: Background An increasing amount of evidence suggests an association between increased intestinal permeability and the pathogenesis of chronic inflammatory diseases. However, the clinical significance of gut barrier dysfunction in psoriasis remains to be established. Objective To evaluate whether there are differences in disease activity, the severity of gastrointestinal symptoms and the blood concentration of bacterial metabolites in psoriatic patients with a normal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…However, the association between HS and increased circulating TMAO levels was still unexplored. In line with our findings, Sikora et al [74] very recently reported that in psoriasis, another chronic, immune-mediated disease of the skin associated with multiple systemic effects, increased circulating TMAO levels were associated with an altered gut barrier, gastrointestinal symptoms, and a systemic inflammatory profile. Of interest, TMAO has been demonstrated to activate pro-inflammatory signaling pathways [3].…”
Section: Discussionsupporting
confidence: 93%
“…However, the association between HS and increased circulating TMAO levels was still unexplored. In line with our findings, Sikora et al [74] very recently reported that in psoriasis, another chronic, immune-mediated disease of the skin associated with multiple systemic effects, increased circulating TMAO levels were associated with an altered gut barrier, gastrointestinal symptoms, and a systemic inflammatory profile. Of interest, TMAO has been demonstrated to activate pro-inflammatory signaling pathways [3].…”
Section: Discussionsupporting
confidence: 93%
“…The present study preliminarily demonstrated the relevance of gut microbiota in the course of psoriasis from several aspects. We first found that multiple gastrointestinal symptoms were significantly more frequent in patients with psoriasis than healthy controls, which may result from compromised intestinal barrier and/or disordered gut microbes ( 32 ). Except for gastric acid reflux, other gastrointestinal symptoms involved in this study were not found to be related to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers unveiled that SCFAs could maintain gut barrier integrity and reduce intestinal permeability so that microbial dysbiosis related to the deregulation of SCFA may associate with “leaky gut” [ 70 , 71 ], and thus lead to the onset of numerous diseases including but not limited to psoriasis. Furthermore, a number of studies showed that an altered intestinal barrier was linked with psoriasis activity and severity through quantifying intestinal barrier integrity markers (such as claudin-3 and intestinal fatty acid binding protein, I-FABP) or the serum concentrations of gut microbiota-associated metabolite trimethylamine N-oxide (TMAO) [ 73 , 74 , 75 , 76 , 77 ]. The enrichment of L-arginine-related pathways and urea cycle intermediates (e.g., citrulline, ornithine, proline) also coincided with previous serum metabolomic studies on psoriasis patients [ 78 ].…”
Section: Discussionmentioning
confidence: 99%